Bioactivity of silverleaf nightshade (Solanum elaeagnifolium Cav.) berries parts against Galleria mellonella and Erwinia carotovora and LC-MS chemical profile of its potential extract - Abdel Nasser A. Kobisi; Mohamed A. Balah; Ahmed R. Hassan (Scientific Reports, 2024)
Abstract Natural products received much attention as an environmentally beneficial solution for pest management. Therefore, the extracts of invasive silverleaf nightshade (Solanum elaeagnifolium Cav.) weeds using their berries parts (seeds, peels and mucilage) supported by bioassay-guided fractionation were tested against both the greater wax moth (Galleria mellonella) and Erwinia carotovora pv. carotovora causes of the blackleg of potatoes. The seeds and peels of S. elaeagnifolium were successively extracted by maceration using dichloromethane (DCM), ethyl acetate (EtOAc), and ethanol (EtOH), respectively. While, its mucilage was extracted using EtOAc. The successive EtOH extract of the plant seeds had promising inhibition efficacy and the best minimal inhibition concentration (MIC) of 50 µg/ml against E. Carotovora amongst other extracts (DCM and EtOAc of the plant berries parts). Depending on dose response activity, EtOH extract had G. mellonella larval mortality and pupal duration rates (LC50; 198.30 and LC95; 1294.73 µg/ml), respectively. Additionally, this EtOH extract of seeds was fractionated using preparative TLC to three characteristic bands. The insecticidal and bacterial activities of these isolated bands (SEA, SEB, and SEC) were evaluated at a dose of 100 µg/ml, causing mortality by 48.48, 62.63 and 92.93% (G. mellonella larvae) and inhibition by 15.22, 0.00 and 31.66 mm (E. carotovora), respectively. Moreover, the separated major three bands were tentatively identified using LC-ESI-MS analysis revealing the presence of two phenolic acids; chlorogenic acid (SEA) and dicaffeoyl quinic acid (SEB) in addition to one steroidal saponin (SEC) annotated as borassoside E or yamoscin. Finally, the plant seeds’ successive EtOH extract as well as its active constituents, exhibited potential broad-spectrum activity and the ability to participate in future pest management initiatives. A field study is also recommended to validate its bio-efficacy against selected pests and to develop its formulations.